The effects of a maximal power training cycle on the strength, maximum power, vertical jump height and acceleration of high-level 400-meter hurdlers - Balsalobre-Fernandez, C.; Tejero-Gonzalez, C. M.; del Campo-Vecino, J.; Alonso-Curiel, D. (Journal of Human Kinetics, 2013)
The aim of this study was to determine the effects of a power training cycle on maximum strength, maximum power, vertical jump height and acceleration in seven high-level 400-meter hurdlers subjected to a specific training program twice a week for 10 weeks. Each training session consisted of five sets of eight jump-squats with the load at which each athlete produced his maximum power. The repetition maximum in the half squat position (RM), maximum power in the jump-squat (W), a squat jump (SJ), countermovement jump (CSJ), and a 30-meter sprint from a standing position were measured before and after the training program using an accelerometer, an infra-red platform and photocells. The results indicated the following statistically significant improvements: a 7.9% increase in RM (Z=-2.03, p=0.021, dc=0.39), a 2.3% improvement in SJ (Z=-1.69, p=0.045, dc=0.29), a 1.43% decrease in the 30-meter sprint (Z=-1.70, p=0.044, dc=0.12), and, where maximum power was produced, a change in the RM percentage from 56 to 62% (Z=-1.75, p=0.039, dc=0.54). As such, it can be concluded that strength training with a maximum power load is an effective means of increasing strength and acceleration in high-level hurdlers.